CD8+ T-cell Immune Evasion Enables Oncolytic Virus Immunotherapy - Aldo Pourchet (EBioMedicine, 2016)
Although counteracting innate defenses allows oncolytic viruses (OVs) to better replicate and spread within tumors, CD8+ T-cells restrict their capacity to trigger systemic anti-tumor immune responses. Herpes simplex virus-1 (HSV-1) evades CD8+ T-cells by producing ICP47, which limits immune recognition of infected cells by inhibiting the transporter associated with antigen processing (TAP). Surprisingly, removing ICP47 was assumed to benefit OV immuno-therapy, but the impact of inhibiting TAP remains unknown because human HSV-1 ICP47 is not effective in rodents. Here, we engineer an HSV-1 OV to produce bovine herpesvirus UL49.5, which unlike ICP47, antagonizes rodent and human TAP. Significantly, UL49.5-expressing OVs showed superior efficacy treating bladder and breast cancer in murine models that was dependent upon CD8+ T-cells. Besides injected subcutaneous tumors, UL49.5-OV reduced untreated, contralateral tumor size and metastases. These findings establish TAP inhibitor-armed OVs that evade CD8+ T-cells as an immunotherapy strategy to elicit potent local and systemic anti-tumor responses.